Kajian terhadap Siklus, Trend, dan Musiman pada Peramalan Saham-Saham Individu pada Saham LQ-45 - SIJABAT, HEBER P. (UI Scholars Hub, 2011)
For investor, stock return is very important. They only interested in stocks that has promised positive returns. Trend analysis, moving average method, seasonal method, and error factor are factors that are greatly affected cycles. This conclusion is backed up by calculation using methods, formulas, regression technique quantitative approach and descriptive methods. In a short period of time, constant trend in moving average itself caused the stock cycle. For LQ-45 stocks, two years period of cycles are affected by seasonal factors. Stock return greatly affected stock price’s ups and downs. However, these techniques only provide prediction, not an exact result.